2004
DOI: 10.1897/03-310
|View full text |Cite
|
Sign up to set email alerts
|

Maternal transfer efficiency and transgenerational toxicity of methylmercury in Daphnia magna

Abstract: We examined maternal transfer efficiency, retention by subsequent generations, and transgenerational toxicity of methylmercury (CH3Hg or MeHg) in a population of freshwater zooplankton (Daphnia magna). The effect of dietary MeHg residence time in the daphnids on the efflux system also was quantified. After ingesting a relatively high dosage of MeHg, D. magna exhibited a reduction of live neonates and an increase of undeveloped eggs (or embryos), which reflected the sublethal toxicity of MeHg. The daily materna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 32 publications
4
37
0
Order By: Relevance
“…However, Daphnia grew faster on high-quality, low C:P algae (''Daphnia responses'' in Table 1) resulting in a significant reduction in the concentration of MeHg in their tissues. Daphnia MeHg efflux rates (Ϸ0.041 d Ϫ1 ) were consistent with those found in other studies (21,22) and were lower than the efflux rates of other heavy metals, such as Cd, Cr, Se, Zn (23), and inorganic Hg (24). Low MeHg efflux rates result in the buildup of high levels of MeHg in somatic tissue.…”
Section: Discussionsupporting
confidence: 88%
“…However, Daphnia grew faster on high-quality, low C:P algae (''Daphnia responses'' in Table 1) resulting in a significant reduction in the concentration of MeHg in their tissues. Daphnia MeHg efflux rates (Ϸ0.041 d Ϫ1 ) were consistent with those found in other studies (21,22) and were lower than the efflux rates of other heavy metals, such as Cd, Cr, Se, Zn (23), and inorganic Hg (24). Low MeHg efflux rates result in the buildup of high levels of MeHg in somatic tissue.…”
Section: Discussionsupporting
confidence: 88%
“…Tsui and Wang (2004) showed that over 70% of a 33.3 ± 1.91 μg/g body burden resulting after a 5 day dietary exposure of MeHg was eliminated over a 20 day period in Daphnia magna . The biological retention half-life was 9.07 ± 0.12 d for MeHg in that study [50]. Assuming a similar half-life in D. pulex , our results suggest that early life exposure may affect survivorship even after the body burden of MeHg is significantly reduced, especially considering the low tissue concentrations measured in the present study (1.9 ppm (ng/mg) as Hg) after the highest dose tested (1600 ng/L).…”
Section: Discussionmentioning
confidence: 91%
“…Tsui and Wang (2004a) also observed in D. magna that the losses due to maternal transfer of mercury ranged from 11 to 15% for inorganic form and from 32 to 41% for organic form of this metal. The same authors, evaluating only the organic form of mercury, found that maternal transfer is the second most important mechanism of loss of this metal (Tsui and Wang 2004b).…”
Section: Discussionmentioning
confidence: 99%